1988
DOI: 10.1111/j.1432-1033.1988.tb13976.x
|View full text |Cite
|
Sign up to set email alerts
|

Reprogrammed expression of subunit 9 of the mitochondrial ATPase complex of Saccharomyces cerevisiae

Abstract: A synthetic gene has been designed and constructed by total chemical synthesis as a first step in the functional relocation from the mitochondrion to the nucleus of a gene encoding subunit 9 of the yeast mitochondrial ATPase complex. This gene (NAP9) incorporates codons frequently used in nuclear genes of Saccharomyces cerevisiae and additionally includes a series of unique restriction enzyme cleavage sites to facilitate future systematic manipulations of the gene and its protein product. Following the express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
2

Year Published

1988
1988
2006
2006

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 24 publications
0
10
2
Order By: Relevance
“…However, a promising therapeutic approach to patients with mtDNA mutation is based on allotopic gene expression (allotopic gene expression is expressing a mitochondrially encoded gene from nucleus transfected constructs as fusion with an Nterminus mitochondrial target sequence). This concept was first developed by Phillip Nagley in Australia in the late 1980s, in Saccharomyces cerevisiae genes (Gearing and Nagley, 1986;Farrell et al, 1988;Law et al, 1988Law et al, , 1990. The first successful mammalian allotopic expression of a mtDNA-encoded polypeptide was shown in 2002 by Manfredi et al (2002).…”
Section: Towards Mitochondrial Therapeuticsmentioning
confidence: 99%
“…However, a promising therapeutic approach to patients with mtDNA mutation is based on allotopic gene expression (allotopic gene expression is expressing a mitochondrially encoded gene from nucleus transfected constructs as fusion with an Nterminus mitochondrial target sequence). This concept was first developed by Phillip Nagley in Australia in the late 1980s, in Saccharomyces cerevisiae genes (Gearing and Nagley, 1986;Farrell et al, 1988;Law et al, 1988Law et al, , 1990. The first successful mammalian allotopic expression of a mtDNA-encoded polypeptide was shown in 2002 by Manfredi et al (2002).…”
Section: Towards Mitochondrial Therapeuticsmentioning
confidence: 99%
“…In a series of experiments, it was demonstrated that the (normally mitoehondrially encoded) subunits 8 and 9 of yeast FoF~-ATPase could be imported and correctly processed by mitochondria (148)(149)(150). For this purpose, synthetic "genes" for these subunits were fused to DNA segments coding for a mitochondrial matrix-targeting signal (presequence) and the constructs were expressed in yeast.…”
Section: Conservative Sortingmentioning
confidence: 99%
“…For import experiments, mitochondria (200 pg protein) were incubated with lo6 dpm 35S-labelled precursor [19]; the incubation buffer (final volume 100 pl) contained 0.6 M sorbitol, 20 mM Hepes/KOH, 40 mM KC1, 8 mM methionine, 1 mM dithiothreitol, 10 mM MgC12, 10 mM succinate, 10 mM malate, 5 mM ATP, pH 7.4 and 40% (by vol.) postribosomal supernatant of rabbit reticulocyte lysate (Promega) prepared by spinning the lysate at 150000 x g for 30 min.…”
Section: Protein Import and Assembly Assays In Vitromentioning
confidence: 99%
“…Following import incubations, mitochondrial proteins were analyzed by SDS/ PAGE either from whole mitochondria, or after lysis and immunoadsorption to collect mtATPase complexes. For the former purpose, the mitochondria in 20 pl of a single-import incubation mixture were simply re-isolated by centrifugation in an Eppendorf microfuge [19]. For the latter purpose, the residual 80-pl portion of the single-import incubation mixture was centrifuged to recover mitochondria, which were then solubilized in 40 p1 cholate extraction buffer (0.5% sodium cholate, 1 % octyl P-D-glucopyranoside, 10 mM p-aminobenzamidine/HCl, 10 mM c-amino-N-hexanoic acid, 2 mM phenylmethylsulphonyl fluoride, 1 mg/ml ATP, 278 mM mannitol, 222 mM sorbitol, 0.56 mM EDTA and 11 mM Tris/ HC1, pH 7.4).…”
Section: Protein Import and Assembly Assays In Vitromentioning
confidence: 99%